2012
DOI: 10.1371/journal.pone.0046055
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Induces Multiple Stress Pathways Including LKB1/AMPK Activation That Regulate Its Cytotoxic Effects in Squamous Cell Carcinoma Cells

Abstract: BackgroundCellular stress responses trigger signaling cascades that inhibit proliferation and protein translation to help alleviate the stress or if the stress cannot be overcome induce apoptosis. In recent studies, we demonstrated the ability of lovastatin, an inhibitor of mevalonate synthesis, to induce the Integrated Stress Response as well as inhibiting epidermal growth factor receptor (EGFR) activation.Methodology/Principal FindingsIn this study, we evaluated the effects of lovastatin on the activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 49 publications
4
59
0
Order By: Relevance
“…On further examination, the mechanisms utilised were identified to involve the depletion of ATP through the inhibition of mitochondrial function or more specifically complex I. [16,49] This feature is attributed to the structural design of the drug, namely tetrahydrofuran rings, which were replaced in this study by ethylene glycol ether units, and as a consequence, there was enhanced efficacy. It was illustrated that the ATP depletion was responsible for the activation of AMPK and inhibition of mTOR with a concomitant autophagic response.…”
Section: Adenosine-5′-triphosphatementioning
confidence: 88%
See 3 more Smart Citations
“…On further examination, the mechanisms utilised were identified to involve the depletion of ATP through the inhibition of mitochondrial function or more specifically complex I. [16,49] This feature is attributed to the structural design of the drug, namely tetrahydrofuran rings, which were replaced in this study by ethylene glycol ether units, and as a consequence, there was enhanced efficacy. It was illustrated that the ATP depletion was responsible for the activation of AMPK and inhibition of mTOR with a concomitant autophagic response.…”
Section: Adenosine-5′-triphosphatementioning
confidence: 88%
“…[15] This was supported by another group that showed that STRAD induced the relocation of LKB1 to the cytoplasm from the nucleus where it is active and is aided by MO25, which stabilises the interaction between LKB1 and AMPK. [16] To date, these findings suggest that SIRT1 could be a plausible key regulator in numerous cancer cell lines given that the tumour microenvironment is akin to that represented in a caloric-restricted model.…”
Section: +mentioning
confidence: 98%
See 2 more Smart Citations
“…1). Indeed, various members of the statin class of cholesterol-lowering medications have been shown to activate AMPK, correct mitochondrial dysfunction and extend longevity in HGPS (Zmpste24 À/À ) mouse models, and increase HIV-1 LTR-driven promoter activity and viral transcription [169,173,174]. Interestingly, HDACs have been shown to modulate alternative splicing by influencing splice site selection and the HDAC inhibitors belinostat, trichostatin A, and vorinostat have each been shown to activate AMPK and reactivate (albeit inefficiently) latent HIV-1 viral reservoirs [175][176][177][178].…”
Section: Ampk Activation and Mitochondrial Atp Production Is Essentiamentioning
confidence: 99%